Development of emission recovery household backyard kiln for charcoa l production - Ongora, Solomon (Kampala, 2015)
Unpublished dissertation (MSc. ENR.)- Makerere University, 2015.
Includes bibliographical references (p. 63-68).
Keywords: Kilns